H-type aggregation of functional metal ion sensing phthalocyanines: Synthesis, characterization and electrochemistry - ÖZKAYA, ALİ RIZA (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
We report, in this study, the preparation and physical characterization of the peripherally functionalized ionophore ligand, 4,5-bis(6-hydroxyhexan-3ylthio)-1,2-dicyanobenzene (1) and its branched thioalcohol-substituted phthalocyanines, 2,3,7,8,12,13,17,18-octakis{6-hydroxyhexan-3-ylthio)-metal (II) or (III) phthalocyanines (M(Pc[SCH(C(3)H(7))(C(2)H(5)OH)](8)) {M = Pb(II) (2), Zn(II) (3), Cu(II) (4), Co(II) (5) and Mn(III), X = Cl(-) (6)) which can selectively bind soft-metal ions such as silver (I) and palladium (II). It was observed by means of UV-Vis absorption spectrophotometry that the aggregates formed lead to a low solubility of the phthalocyanines in protic solvents, such as low molecular alcohols. However, the addition of AgNO(3) and Na(2)PdCl(4) into a THF-MeOH solution of {M{Pc[SCH(C(3)H(7))(C(2)H(5)OH)](8)X) (M = Pb(II) (2), Zn(II) (3), Cu(II) (4), Co(II) (5) and Mn(III), X = Cl- (6)) induced optical changes, which indicated the formation of twisted H-type dimers (blue shift, face-to-face fashion) of (M(Pc[SCH(C3H7)(C2H5OH)18) complexes, bound by four PdCl(2) and AgNO(3) units in THF solution. Elemental analysis data, matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF/MS), FT-IR, (1)H, (13)C NMR, and UV-Vis spectral data were used as complementary techniques. Voltammetry and in situ spectroelectrochemistry of the complexes were performed on Pt in DMSO/TBAP. The first reduction and oxidation processes of 5 were found to be split due to the presence of facile equilibria between the species coordinated differently at axial positions. The Mn(III)Pc(-2)X(-) complex (6) displayed well-defined colour changes during its reduction processes. The redox behaviour of the Mn(III)Pc( -2)X- complex was observed to be affected significantly by the existence of oxygen in solution due to the formation of mu-oxo MnPc species, Mn(III)Pc-O-PcMn(III). This effect was clarified well by in situ spectroelectrochemical measurements. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Metallophthalocyanine; H-type aggregation; Metal ion sensing; Spectroscopy; Electrochemistry and spectroelectrochemistry; MANGANESE PHTHALOCYANINES; COMPLEXES